Pattern of hepatitis B and C infection among gravid women and their newborns in a tertiary care infirmary in India - Marwah, Sheeba; Mohindra, Ritin; Sharma, Sushmita; Mohan, Praveen V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective is to determine the prevalence of the hepatitis B and C virus among pregnant women, to assess impact of maternal hepatitis B virus (HBV) or hepatitis C virus (HCV) carrier status on pregnancy outcomes and to gauge the risk factors associated with them. Antenatal clinic attenders and women undergoing termination of pregnancy over three years. Methods: The study was conducted in Gian Sagar Medical College & Hospital, Patiala, Punjab, India. Hepatitis B antigen and Hepatitis C virus antibody testing of sera from specimens sent to the hospital laboratory for routine serological testing. The results were then linked to risk information, obstetric complications and pregnancy outcome. Results: Overall HBsAg and anti-hepatitis C antibody prevalence was 1.2% (33/2031). Increased risk of transmission was associated with sexually transmitted diseases and previous surgical procedures. High rates of preterm labor pains, CD (27.27%), and non-reassuring fetal heart rate patterns and meconium stained liquor were found in the seropositive patients. Conclusions: Maternal hepatitis B and C carrier status is an eminent risk factor for adverse pregnancy outcome.